Effects of two Intervention strategies on achievement in sociology of education among NCE part-time students in some colleges of education centres in Ibadan (2014)
Reading skill and self-efficacy techniques were used as intervention strategies in enhancing academic achievement of sandwich learners in colleges of education. The pre-test, post test, control, quasi experimental design with 3x2x2 factorial matrix was adopted. Non proportional random sampling technique was used to select sandwich freshmen from the three state colleges of education sandwich centres in Ibadan. Cap method was used to select 50 participants each from each centre assigned to study’s skill (SS) self efficacy (SE) and control group (CG). Three hypotheses were tested at 0.05 level of significance. Three instruments were used; study skill assessment scale (r=0.79), self efficacy scale (r=0.85) and Sociology of Education Achievement Test (r=0.93). The data collected were analyzed using Simple Percentage, Frequency Count, Analysis of covariance (ANCOVA), multiple classification analysis (MCA) and descriptive statistics of mean and standard deviation. There was significant main effect of the treatment on the academic achievement of the participants (F3, 146 - 77.203, P < .05, η2 = .514). There was significant main effect of marital status (F2, 147= 10.414, P < .05 η2 = .066) while there was no significant main effect of gender (F2, 147 = .869, P >.05, η2 = .000). Reading skill and self efficacy strategy were effective in enhancing academic achievement of sandwich learners in colleges of education. Therefore, they should be introduced in colleges of education to enhance the academic achievement of sandwich learners.